Effect of vaginal microbiota on pregnancy outcomes of women from Northern China who conceived after IVF - Tong, Yu; Sun, Qiang; Shao, Xiaoguang; Wang, Zhijian (Frontiers in Endocrinology, 2023)
Objective: This study aimed to investigate the correlation between vaginal microbiota and pregnancy outcomes of women who achieved pregnancy via in vitro fertilization (IVF) in Northern China, and to determine a biomarker for evaluation of the risk of preterm births in these women.In total, 19 women from Northern China women who conceived after IVF and 6 women who conceived naturally were recruited in this study. The vaginal samples of the healthy participants were collected throughout pregnancy, that is, during the first, second, and third trimesters. The V3-V4 region of 16S rRNA was used to analyze the vaginal microbiome, and the bioinformatic analysis was performed using QIIME Alpha and Beta diversity analysis.Results: Either IVF group or Natural conception group, bacterial community diversities and total species number of vagnal samples from who delivered at term were significantly higher than those who delivered before term. Low abundance of vaginal bacteria indicates an increased risk of preterm delivery. Further, more abundant vaginal bacteria was found in first trimesters instead of the next two trimesters. Vignal samples collected during first trimester showed richer differences and more predictive value for pregnancy outcoes. In addition, the diversity of the vaginal bacterial community decreased as the gestational age increased, in all samples. Alloscardovia was only found in participants who conceived after IVF, and the percentage of Alloscardovia in viginal samples of normal delivery group is much higher than the samples from preterm delivery group.Vobrio specifically colonized in vagina of pregnant woman in AFT group (those who conceived after IVF (A), first trimester (F), and delivered at term (T))and Sporosarcina was detected only in women with AFT and AST (those who conceived after IVF (A), second trimester (S), and delivered at term (T)). These data indicates that Alloscardovia, Vobrio and Sporosarcina have great potential in predicting pregnancy outcomes who pregnanted by vitro fertilization Conclusions: Vaginal microbiota were more stable in women who conceived naturally and those who carried pregnancy to term. Oceanobacillus might act as a positive biomarker, whereas Sulfurospirillum and Propionispira may act as negative biomarkers for the risk of preterm birth.